Kandungan Gula Dalam Minuman Teh Susu Dengan Topping Boba: Kandungan Gula Sangat Tinggi dalam Minuman Teh Susu dengan Topping Boba - Mayrlnn Trifosa Veronica; Ibnu Malkan Bakhrul Ilmi; Yessi Crosita Octaria (Amerta Nutrition, 2022)
Background: The prevalence of overweight and obesity have been climbing overtime in all age groups in Indonesia, this increase is in paralel to increasing prevalence of chronic non-communicable diseases. While on the other hand consumption of sweet sweetened beverages as an important risk factor is also in dramatic rise, with the consumption of milk tea as an example has been growing up to 8500% since 2018. Objectives: this study aimed to assess the sugar content in this type of drink. Methods: Analysis of sugar content (fructose, glucose, sucrose) was done using the high-performance liquid chromatography (HPLC) method and the total calorie analysis was obtained from adding up calories from protein, fat, carbohydrate components or by calculation method. Results: This study shows that the current drink of milk tea with boba topping has high sugar and calorie content. One large glass of boba milk tea contains 47.21 grams of dietary sugar (glucose, fructose, sucrose) and 675 kcal calories. Conclusions: Boba milk tea drinks are very high in sugar and calories content